PENGORGANISASIAN PERENCANAAN DESA: KAJIAN DI DESA KALONGSAWAH KECAMATAN JASINGA KABUPATEN BOGOR - Karyana, Ayi (Jurnal Organisasi dan Manajemen, 2011)
Development Planning Consultation (Musrenbang) Village is an annual discussion forum of villages stakeholders to agree on Village Development Work Plan (RKP Village) in the planned budget. This study aims to describe and analyze: 1) formation of Musrenbangdes Organizing Team (TPM), 2) formation of village Musrenbang Team Guide by TPM; 3) preparation of technical implementation village Musrenbang; and 4) a participatory rural assessment and dialogue. Writing method used in this study is descriptive analysis. The study shows, in the process of team formation TPM, the preparation of TPM personnel is the right and depends on the Village Head. TPM in performing their duties do not form a team or guides Working Group (WG), whereas the normative should be formed. The Working Group role and duty are process designer, managing the process from pre-to post-musrenbangdes stage, as the manager of a meeting or discussion forum and as a source of information. In the process of technical preparation through the stages of implementation, Musrenbangdes does not begin with Deliberation Hamlet (Musdus), there is no agenda for preparing the implementation plan of village workshops, Village Representative Body (BPD) does not specifically implement Musrenbangdes agenda. Village Assessment Team was not formed, so there is no village study to compile data / information on the latest village issues. Organizing musrenbang villages in the Village District Kalongsawah Jasinga Bogor Regency, ranging from the establishment of Village TPM Team Guide/ Working Group, technical preparation and review of the implementation of village meetings in a participatory and dialogical were not implemented optimally.